STANDARD OF QUALITY ASSURANCE OF BASIC ISLAMIC SECONDARY IN INDONESIA - Muhamad - Nizam; Junita Dwi Wardhani (Jurnal Ilmiah Pesantren, 2017)
Education quality assurance is an integral part of the education system Indonesian from early childhood to the high education. From approximately 215.356 schools, there are more than 50.000 primary to secondary education which is managed by the foundation of Islam and religious affairs ministry. Only about 37% institution were accredited. This means about 63% were still below national standard of education. Number of islamic education institution are quite a lot and there are many education institutions do not meet with the national quality assurance standard and give quality of graduated is not as expected. This paper aims to present about the need for standardization of quality assurance from the Islamic primary and secondary education in rder to unite and chsrscterize SNPs Kemendikbud that incorporate with Al-Quran and Al-Hadits as guidelines. This standard need to be formulated by forum composed of representativesof the institutions that organize school / madrasah islam in Indonesia, so the curriculum developed to meet the expected learning outcomes either Islamic standard education or KKNI.